Combination of Two Targeted Medications (Bevacizumab Plus Cetuximab) Improve the Therapeutic Response of Pancreatic Carcinoma. Issue 15 (April 2016) - Tai, Cheng-Jeng; Huang, Ming-Te; Wu, Chih-Hsiung; Wang, Chien-Kai; Tai, Chen-Jei; Chang, Chun-Chao; Hsieh, Cheng-I.; Chang, Yu-Jia; Wu, Chang-Jer; Kuo, Li-Jen; Wei, Po-Lei; Chen, Ray-Jade; et al.
Abstract : Abstract: The objective of this study is to evaluate the efficacy and safety profiles of the targeted medications, bevacizumab and cetuximab, in combination with cytostatic drugs in patients with locally advanced or metastatic pancreatic cancer. In this retrospective phase 2 study, a total of 59 patients with pancreatic cancer were recruited and received conventional (gemcitabine, cisplatin, and fluorouracil) or targeted regimen (conventional plus bevacizumab and cetuximab for the first cycle) in 2-week intervals for four cycles. The primary end-point for this study was the overall response rate. Secondary end-points were progression-free survival and the safety profiles of the combined therapy. The median time-to-progression and overall survival were 3 and 7 months, respectively, in the conventional treatment group as well as 11 and 13 months, respectively, in the targeted medications treatment group. The most common adverse events in both treatment groups were nausea and vomiting. Moderate (Grade 2) nausea and vomiting were more common in the conventional group than the targeted group but severe (Grade 3) nausea and vomiting were more common in the targeted group. Bevacizumab and cetuximab in combination with gemcitabine, cisplatin, and fluorouracil may help lengthen overall survival up to six months for patients with pancreatic cancer.